Spatial dynamics of female snow crab (Chionoecetes opilio) in the Eastern Bering Sea - Ernst, Billy; Orensanz, Jose Maria; Armstrong, David A (Canadian Journal of Fisheries and Aquatic Sciences)
Snow crab (Chionoecetes opilio) migrations in the eastern Bering Sea have long been ignored. Based onpreliminary information, we hypothesized that females undergo an extensive ontogenetic migration, tracking downenvironmental gradients. We analyzed a 25-year time series of survey data and defined ontogenetic stages in terms of a“shell condition index” calibrated with radiochemical methods. “Pseudo-cohorts” of mature females (groups of femalesthat undergo puberty molt in a given year) “recruit” to the mature female pool in the Middle Domain (50–100 m) ofthe intermediate shelf. Females undergo puberty molt and primiparous mating in winter. Over the next year, they migratean average net distance of 73.5 nautical miles towards the shelf edge following a predominantly northeast–southwest direction. Maximum post-terminal molt life span is 6–7 years. Results support the hypothesis that thevariable tracked is near-bottom temperature. Although near-bottom temperature fields vary from year to year, thecorresponding vector field is a conservative template, which explains the consistency observed in the pattern ofmigration. Elucidation of the life history schedule of mature female snow crabs in the eastern Bering Sea revealed thatit is very similar to that reported for eastern Canada, although patterns of migration may differ substantially betweenthe two systems. Fil: Ernst, Billy. University of Washington; Estados Unidos Fil: Orensanz, Jose Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Armstrong, David A. University of Washington; Estados Unidos